Operator (p, η)-Convexity and Some Classical Inequalities - Chuanjun Zhang; Muhammad Shoaib Saleem; Waqas Nazeer; Naqash Shoukat; Yongsheng Rao (Journal of Mathematics)
In this paper, we will introduce the definition of operator p,η-convex functions, we will derive some basic properties for operator p,η-convex function, and also check the conditions under which operations’ function preserves the operator p,η-convexity. Furthermore, we develop famous Hermite–Hadamard, Jensen type, Schur type, and Fejér’s type inequalities for this generalized function.